Effect of biofertilizers in improving production of hot pepper (Capsicum annuum L.), and tolerating drought stress - Yaseen, Arshad Abdulkhalq; Ahmed, Sherwan Jalil; Bakr, Triska Dlshad (Zanco Journal of Pure and Applied Sciences, 2024)
Chili peppers (Capsicum annuum L.) are one of the most widely planted vegetables all over the world since it has several health advantages and add a delicious flavor to a range of recipes. Drought stress is accounted as the most abiotic environmental condition that can negatively impact the quality and production of many crops. In this context, a factorial randomized design study was conducted in open field pots to determine how irrigation deficit affects the plant's agronomic and physiological characteristics. Capsicum spp. was subjected to three drought stress conditions (once every day, once every two days, and once every three days representing light or low, moderate, and severe drought stress). At the same time, biostimulants Alga600, moringa leaf extract (MLE), and homemade fertilizer (H-made) were foliar sprayed to determine whether they might minimize abiotic stress or increase plant susceptibility to drought. The results demonstrate that severe drought stress resulted in a considerable drop in fruit quality and production, followed by moderate and light drought. Whereas, minimum chlorophyll and carotenoids are influenced by deficient irrigation. On the other hand, biostimulants could mitigate the detrimental impact of drought stress on yield, chlorophyll concentration, and other physical characteristics such as leaf area. Among the biostimulants, Alga600 had the greatest impact on increasing chili pepper stress tolerance, followed by 6% MLE and H-made biostimulants when compared to their controls (plants treated with deionized water only). However, the combination of biostimulants with drought stress was more obvious in drought roses. The interaction was less influenced by the drought, which intensified the physical and economic aspects. While some biostimulants, such as MLE and Alga600, may have a greater impact on plant production and pigment content as drought stress increases. The correlation coefficient also indicates that the measured parameters had both positive and negative correlations to each other. Physical parameters like leaf area, number of fruits, fruit diameter, and length have a significant positive correlation to the total yield while chlorophyll content can have a positive and negative correlation to the physical parameters.